Stock prices, foreign opportunity cost, and money demand in Malaysia: a cointegration and error correction model approach - Mohd Zaini Abd Karim,; Tang, Boon Guan (Penerbit Universiti Kebangsaan Malaysia, 2004)
The main purpose of this study is to investigate the relevance of stock price and foreign opportunity cost variables to the money demand function in Malaysia using quarterly data over the period of 1982:1 to 1998:2 by employing recently developed econometric techniques of cointegration and error correction modeling. To take into account the effect of Asian Financial Crisis in mid 1997 on the behavior of the demand for money in Malaysia, the sample period is divided into two sub-samples: 1982:1 to 1996:4 and 1982:1 to 1998:2. The results provide evidence that the crisis somewhat affect the behavior of the money demand. The results of the study also show that the real money balances, real income, money’s own rate of return, the rate of return of alternative assets, stock prices, expected exchange rate depreciation and foreign interest rate are cointegrated suggesting the existence of a stable long run relationship among them in spite of the financial liberalization and innovation process that the Malaysian financial system has been experiencing. In addition, the results also indicate the dominance of wealth effect over substitution effect and the presence of currency substitution in Malaysia.